Graded porous carbon electrode material, in-situ activation preparation method, electrode plate and application

The natural materials are heat treated in a high-temperature cracking furnace through in-situ activation method to form porous carbon materials with high specific surface area and high mesoporous content, which solves the performance and environmental problems of existing porous carbon materials in electrochemical energy storage devices, and realizes an efficient and low-cost preparation process.

CN119706836APending Publication Date: 2025-03-28QINGHAI HUANGHE HYDROPOWER DEVELOPMENT CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311260087.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing porous carbon materials have problems such as low specific surface area, unreasonable pore structure, low macropore/mespore content, complex production process, high product cost, and unfriendly environment in electrochemical energy storage devices.

Method used

In situ activation method is used to heat-treat natural materials in a high-temperature cracking furnace, and synchronous carbonization and activation are used to form a porous carbon material with a large-pore-mesoporous-micropore graded pore structure.

Benefits of technology

The preparation of porous carbon materials with high specific surface area and high mesoporous content is achieved, the electrochemical performance of electrochemical energy storage devices is improved, the production process is simplified, the cost is reduced, and environmental pollution is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706836A_ABST
    Figure CN119706836A_ABST
Patent Text Reader

Abstract

The invention discloses a graded porous carbon electrode material, an in-situ activation preparation method, an electrode plate and application, and relates to the technical field of electrochemical energy storage materials, and the preparation method comprises the following steps: S1, pretreatment: soaking a natural material in an ethanol aqueous solution with a volume fraction of 70-80%, then treating the natural material in boiled distilled water, and drying; s2, in-situ activation: putting the natural material pretreated in the step S1 into a high-temperature cracking furnace chamber, and carrying out heat treatment in the presence of inert gas; s3, purification: soaking the crude product prepared in the step S2 in an ethanol water solution with the volume fraction of 50-70%, filtering, collecting the product, and drying to prepare the purified graded porous carbon material. The invention provides a novel porous carbon material preparation process which is simple in process, short in period, low in cost and capable of effectively reducing environmental pollution and providing a new view for utilization of pyrolysis gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy storage materials, and in particular to a graded porous carbon electrode material and an in-situ activation preparation method, an electrode sheet and applications. Background Art

[0002] Porous carbon (also known as activated carbon) materials have many advantages such as high specific surface area, good conductivity, wide precursor sources, low cost, excellent chemical stability and easy processability. As electrode materials, they have great application potential in new electrochemical energy storage devices such as supercapacitors, lithium-ion batteries, and sodium-ion batteries.

[0003] Porous carbon materials can be produced by methods that require exogenous activators, such as physical activation, chemical activation, and physical-chemical coupling activation. Among them, the physical activation method is also called gas activation, which is a method for preparing porous carbon materials by reacting a carbonized precursor with a physical activator such as water vapor, CO, flue gas (a mixture of water vapor, CO2, N2, etc.), or air at high temperature; the chemical activation method is a method in which a chemical activator (H3PO4, KOH, K2CO3, and ZnCl2, etc.) is added to the precursor in a certain proportion, and carbonized and activated simultaneously after a period of mixed impregnation; the physical-chemical coupling activation method is a two-step activation method that combines chemical activation with physical activation, which first impregnates the precursor with a chemical activator to increase the activity of the precursor, forms a channel for transporting the activated gas inside, and then introduces a physical activation gas at high temperature for physical activation. At present, most commercial porous carbon materials are produced by physical activation, and their specific surface area is small and mainly contributed by a large number of ultrafine pores. When used as an electrode material, it is difficult for electrolyte ions to enter, resulting in limited electrochemical performance. The porous carbon materials prepared by chemical activation method have achieved larger specific surface area and higher macropore / mesopore content, but their disordered pore structure is not suitable for efficient migration of electrolyte ions. In addition, chemical activation method will also cause serious environmental pollution and equipment corrosion. Physical-chemical coupling activation method integrates the advantages of physical activation method and chemical activation method. The prepared porous carbon materials have larger specific surface area and adjustable pore structure, but the process is more complicated and the production cost is high.

[0004] In recent years, some literatures have reported a new self-activation method for preparing porous carbon materials without using exogenous activators. The literature "C. Bommier, R. Xu, W. Wang, et al. Self-activation of cellulose: A new preparation methodology for activated carbon electrodes in electrochemical capacitors, Nano Energy, 13 (2015) 709-717" found that the self-activation phenomenon controlled by the flow rate of inert gas during cellulose pyrolysis can increase the specific surface area of ​​the prepared porous carbon material within a certain range (98-2600 m 2 / g) adjustment. However, due to the microporous structure characteristics of the product, its rich specific surface area cannot be fully utilized when used as an electrode material. The literature "J. He, D. Zhang, M. Han, et al. One-step large-scale fabrication of nitrogen doped microporous carbon by self-activation of biomass for supercapacitors application, J. Energ. Storage 21 (2019) 94-104" achieved the self-activation of cellulose in celery and obtained a specific surface area of ​​up to 1186 m 2 / g porous carbon materials, but the smaller pore size and lower mesopore content (27.3-31.3%) of the product limit its application in organic electrolytes with larger ion sizes, resulting in limited energy density of electrochemical energy storage devices. The literature "X.Hao, J.Wang, B.Ding, et al.Bacterial-cellulose-derivedinterconnectedmeso-microporous carbon nanofiber networks as binder-free electrodes for high-performance supercapacitors, J.Power Sources 352 (2017) 34-41" reports a silica-assisted self-activation method, in which bacterial cellulose is pyrolyzed in a confined nanospace to prepare a mesoporous-dominated hierarchical porous carbon material. Although the product can achieve excellent electrochemical performance as an electrode material, the silica-assisted self-activation method used is complex and costly. In addition, the hydrofluoric acid used in the subsequent removal process of the silica nanoshell is highly corrosive and dangerous. Although these early works demonstrated the self-activation behavior of cellulose-based materials during pyrolysis, there is still no facile self-activation method to date that can convert economical and environmentally friendly precursors into hierarchical porous carbon materials with high specific surface area and high mesopore content.

[0005] In addition, the porous carbon materials for electrochemical energy storage devices prepared by the prior art have problems such as low specific surface area, unreasonable pore structure, low macropore / mesopore content, complex production process, high product cost, and environmental unfriendliness. Therefore, providing a low-cost, "green" preparation method for hierarchical porous carbon materials with both high specific surface area and high mesopore content is an important issue that needs to be solved urgently. Summary of the invention

[0006] The purpose of the present invention is to provide a hierarchical porous carbon electrode material and an in-situ activation preparation method, an electrode sheet and an application. The present invention proposes a low-cost, "green" preparation method for hierarchical porous carbon materials with both high specific surface area and high mesopore content; in view of the shortcomings of existing physical / chemical activation technology, natural materials are converted into high-performance porous carbon materials through an in-situ activation method without using exogenous physical / chemical activators, and the natural hierarchical structure of the raw materials is converted into a macroporous-mesoporous-microporous hierarchical pore structure after in-situ activation, which is more conducive to the diffusion of electrolyte; in view of the pollution problem of pyrolysis gas of organic precursors, by effectively utilizing the structural and component advantages of cellulose-based natural materials, low-cost natural materials are used as raw materials and activators at the same time, pyrolysis gas is efficiently utilized and pollutant gas emissions are reduced.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides an in-situ activation preparation method of a hierarchical porous carbon material, the method comprising the following steps:

[0009] Step S1, pretreatment: soaking the natural material in a 70-80% ethanol aqueous solution at 60-70° C. for 2-3 hours; then soaking the soaked natural material in boiling distilled water for 1-2 hours, and drying at 70-80° C.;

[0010] Step S2, in-situ activation: the natural material pretreated in step S1 is placed in a high-temperature cracking furnace chamber, and the natural material is heat-treated in the presence of 0-0.15 MPa inert gas; before the heat treatment begins, the air in the high-temperature cracking furnace chamber is replaced with inert gas, and no external gas is introduced into the high-temperature cracking furnace chamber during the heat treatment;

[0011] Step S3, purification: the crude product prepared in step S2 is immersed in a 50-70% ethanol aqueous solution at 60-70°C for 2-3h, the product is collected by filtration and dried at 50-60°C to prepare a purified hierarchical porous carbon material.

[0012] As a preferred implementation, in step S1, the natural material types include: sisal fiber, jute fiber, kapok fiber or bamboo fiber.

[0013] As a preferred implementation, the inert gas includes: high-purity nitrogen, argon or helium.

[0014] As a preferred embodiment, in step S2, the heat treatment conditions include: the heating rate of the high-temperature cracking furnace chamber is 5-10°C / min, the heat treatment temperature is 600-1200°C, and the heat treatment time is 2-4h.

[0015] The present invention also provides a hierarchical porous carbon material, which is prepared by adopting the above in-situ activation method.

[0016] The present invention also provides an electrode sheet, which is prepared by the following method:

[0017] The hierarchical porous carbon material is mixed with a conductive agent and a binder, uniformly coated on a metal current collector sheet, and dried at 50-60° C. to prepare an electrode sheet.

[0018] As a preferred embodiment, the mass percentage of the hierarchical porous carbon material to the conductive agent and the binder is (70-85): (10-20): (5-10).

[0019] As a preferred implementation, the metal current collector is aluminum foil or copper foil.

[0020] The present invention also provides an application of an electrode sheet, wherein the electrode sheet is applied to a supercapacitor, a lithium ion battery or a sodium ion battery.

[0021] As a preferred embodiment, in the application of supercapacitor, the electrode sheet is used as both a positive electrode sheet and a negative electrode sheet;

[0022] In the application of lithium-ion batteries, the electrode sheet is a negative electrode sheet;

[0023] In the application of sodium ion batteries, the electrode sheet is a negative electrode sheet.

[0024] As a preferred implementation, in the application of the supercapacitor, the mass ratio of the positive electrode sheet to the negative electrode sheet is 1:1.

[0025] Technical effects and advantages of the present invention:

[0026] (1) The present invention uses a novel simultaneous carbonization / activation process to convert natural materials with a hierarchical structure into porous carbon materials with high specific surface area and high macropore / mesopore content suitable for electrochemical energy storage devices; the raw materials are converted into a macropore-mesopore-micropore hierarchical pore structure after carbonization / activation treatment, which is more conducive to the diffusion of the electrolyte.

[0027] (2) The present invention induces an in-situ activation reaction during the pyrolysis of natural materials without using exogenous physical / chemical activators, auxiliary materials, or flowing protective atmosphere.

[0028] (3) The present invention can adjust the specific surface area, pore volume and pore structure of the product by adjusting the gas pressure in the cracking furnace chamber before heat treatment, the heat treatment temperature and the heat treatment time, thereby determining its electrochemical performance as an electrode material in an electrochemical energy storage device. By increasing the gas pressure in the cracking furnace chamber, the specific surface area, total pore volume and mesopore content of the prepared graded porous carbon material will be significantly increased; by increasing the heat treatment temperature or the heat treatment time, the specific surface area, total pore volume and mesopore content of the prepared graded porous carbon material will also be increased simultaneously.

[0029] (4) The hierarchical porous carbon material prepared by the present invention can be used to prepare positive and negative electrode sheets of supercapacitors, and negative electrode sheets of lithium-ion batteries and sodium-ion batteries.

[0030] (5) The present invention provides a new preparation process for porous carbon materials for electrochemical energy storage devices and other fields that heavily rely on carbon materials with developed pore structures. This process is simple, short-cycle, and low-cost, which can effectively reduce environmental pollution and provide a new perspective for the utilization of pyrolysis gas.

[0031] Other features and advantages of the present invention will be described in the following description, and partly become obvious from the description, or be understood by implementing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a flow chart of an in-situ activation preparation method of a hierarchical porous carbon electrode material of the present invention;

[0033] Figure 2 This is a whole scanning electron microscope image of the hierarchical porous carbon material prepared using sisal fibers in Example 1 of the present invention;

[0034] Figure 3 This is a scanning electron microscope image of a cross section of a hierarchical porous carbon material prepared using sisal fibers in Example 1 of the present invention;

[0035] Figure 4 This is the isothermal nitrogen adsorption-desorption curve of the hierarchical porous carbon material prepared by using sisal fiber in Example 1 of the present invention;

[0036] Figure 5 This is a pore size distribution curve of a graded porous carbon material prepared using sisal fiber in Example 1 of the present invention;

[0037] Figure 6 This is a surface scanning electron microscope image of a hierarchical porous carbon material prepared using kapok fibers in Example 2 of the present invention;

[0038] Figure 7 This is a scanning electron microscope image of a longitudinal section of a hierarchical porous carbon material prepared using jute fibers in Example 3 of the present invention;

[0039] Figure 8 This is the internal pore structure of the hierarchical porous carbon material prepared using bamboo fibers in Example 4 of the present invention. DETAILED DESCRIPTION

[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] In a first aspect, the present invention discloses an in-situ activation preparation method of a hierarchical porous carbon material. Figure 1 The flowchart of the in-situ activation preparation method of a hierarchical porous carbon electrode material of the present invention is as follows: Figure 1 As shown, the method comprises the following steps:

[0042] Step S1, pretreatment: soaking the natural material in a 70-80% ethanol aqueous solution at 60-70° C. for 2-3 hours; then treating the natural material in boiling distilled water for 1-2 hours, and drying in an oven at 70-80° C.;

[0043] Step S2, in-situ activation: 10-40 g of the natural material pretreated in step S1 is placed in a high-temperature cracking furnace chamber, and the natural material is heat-treated for 2-4 hours in the presence of an inert gas at a certain pressure; the high-temperature cracking furnace chamber is arranged to accommodate pyrolysis gas and prevent gas outside the chamber from entering;

[0044] Step S3, purification: the crude product prepared in step S2 is immersed in a 50-70% by volume ethanol aqueous solution at 60-70°C for 2-3h, the product is collected by filtration and dried in an oven at 50-60°C to prepare a purified hierarchical porous carbon material.

[0045] In step S1 of the present invention, the natural material is mainly composed of cellulose, and has vessels and tracheids arranged in parallel along the fiber direction. The types of natural materials include but are not limited to sisal fiber, jute fiber, kapok fiber, and bamboo fiber.

[0046] In step S2 of the present invention, the air in the pyrolysis furnace chamber is replaced with an inert gas before the heat treatment begins, and no external gas is introduced into the pyrolysis furnace chamber during the heat treatment. The inert gas includes high-purity nitrogen, argon or helium, etc., and the pressure of the inert gas is determined according to the desired performance of the porous carbon material.

[0047] Further, the pressure of the inert gas in the cracking furnace chamber is between 0-0.15MPa;

[0048] Preferably, the pressure of the inert gas in the cracking furnace chamber is between 0.05-0.15 MPa;

[0049] More preferably, the pressure of the inert gas in the cracking furnace chamber is between 0.1-0.15 MPa.

[0050] Further, the heat treatment temperature is 600-1200°C;

[0051] Preferably, the heat treatment temperature is 800-1200°C;

[0052] More preferably, the heat treatment temperature is 1000-1200°C.

[0053] Furthermore, the heating rate of the high-temperature cracking furnace chamber is 5-10°C / min.

[0054] In the second aspect, the present invention discloses a hierarchical porous carbon material. The hierarchical porous carbon material prepared by the above-mentioned in-situ activation method does not require the use of exogenous physical activators (carbon dioxide, water vapor, etc.) and chemical activators (potassium hydroxide, zinc chloride, phosphoric acid, etc.).

[0055] In a third aspect, the present invention discloses an electrode sheet, which is prepared by the following method:

[0056] The graded porous carbon material is mixed with a conductive agent and a binder in a certain proportion, uniformly coated on a metal current collector sheet, and dried in an oven at 50-60° C. to prepare an electrode sheet.

[0057] Furthermore, the mass percentage of the hierarchical porous carbon material, the conductive agent and the binder is (70-85): (10-20): (5-10);

[0058] Preferably, the mass percentage of the hierarchical porous carbon material to the conductive agent and the binder is (80-85):(10-15):(5).

[0059] Furthermore, the metal current collector is aluminum foil or copper foil.

[0060] In a fourth aspect, the present invention discloses an application of an electrode sheet, wherein the electrode sheet is applied to a supercapacitor, a lithium-ion battery or a sodium-ion battery.

[0061] Furthermore, in the application of supercapacitors, the electrode sheet is used as both a positive electrode sheet and a negative electrode sheet;

[0062] Preferably, in the application of supercapacitors, the mass ratio of the positive electrode sheet to the negative electrode sheet is 1:1.

[0063] Furthermore, in the application of lithium-ion batteries, the electrode sheet is a negative electrode sheet.

[0064] Furthermore, in the application of sodium ion batteries, the electrode sheet is a negative electrode sheet.

[0065] Example 1

[0066] Embodiment 1 of the present invention provides an in-situ activation preparation method of a hierarchical porous carbon material for an electrochemical energy storage device, the method comprising the following steps:

[0067] Step S1, pretreatment: the natural material (sisal fiber) is placed in an ethanol aqueous solution with a volume fraction of 80% and immersed at 70° C. for 3 hours; then the natural material is treated in boiling distilled water for 2 hours, and dried in an oven at 80° C.;

[0068] Step S2, in-situ activation: 40 g of the natural material pretreated in step S1 is placed in a high-temperature cracking furnace chamber, and before the heat treatment begins, the air in the high-temperature cracking furnace chamber is replaced with high-purity argon gas, and then the chamber is closed and the air pressure in the chamber is adjusted to 0.15 MPa, and the furnace chamber is heated to 1000° C. at a heating rate of 10° C. / min, and the sisal fiber is heat treated at this temperature for 4 hours; the high-temperature cracking furnace chamber is arranged to accommodate pyrolysis gas and prevent gas outside the chamber from entering;

[0069] Step S3, purification: the crude product prepared in step S2 is immersed in a 70% by volume ethanol aqueous solution at 70° C. for 3 h, the product is collected by filtration and dried in an oven at 60° C. to prepare a purified hierarchical porous carbon material.

[0070] Embodiment 1 of the present invention further provides an electrode sheet, which is prepared by the following method:

[0071] The graded porous carbon material purified in step S3 was mixed with a conductive agent and a binder in a mass percentage of 85:10:5, uniformly coated on an aluminum foil current collector sheet, and dried in an oven at 60° C. to prepare an electrode sheet.

[0072] Figure 2 This is a whole scanning electron microscope image of the hierarchical porous carbon material prepared using sisal fibers in Example 1 of the present invention; Figure 3 : is a cross-sectional scanning electron microscope image of a hierarchical porous carbon material prepared using sisal fibers in Example 1 of the present invention; Figure 2-3 As shown, the hierarchical porous carbon material prepared using sisal fiber retains the honeycomb structure of sisal fiber, and the in-situ activation process does not damage its original structure.

[0073] Figure 4 : isothermal nitrogen adsorption-desorption curve of the hierarchical porous carbon material prepared by using sisal fiber in Example 1 of the present invention; Figure 4 As shown in Figure 2, the prepared hierarchical porous carbon material exhibits a type I / IV mixed N2 isothermal adsorption-desorption curve. The sharp rise of the isotherm when the relative pressure (P / Po) is lower than 0.01 and the significant H3 type hysteresis loop when the P / Po is higher than 0.4 confirm the high specific surface area of ​​the sample (1782m 2 / g) and the coexistence of mesopores and micropores, with the mesopore content reaching 68.3%.

[0074] Figure 5: is the pore size distribution curve of the graded porous carbon material prepared by using sisal fiber in Example 1 of the present invention; Figure 5 As shown, the pore size distribution of the prepared hierarchical porous carbon material is concentrated in 0.7-3.9, 5.8-11.2, 15.1-18.3, 22.2-28.0 and 39.8-47.3 nm, indicating the formation of a multi-scale pore structure.

[0075] Example 2

[0076] Embodiment 2 of the present invention provides an in-situ activation preparation method of a hierarchical porous carbon material for an electrochemical energy storage device, the method comprising the following steps:

[0077] Step S1, pretreatment: the natural material (sisal fiber) is placed in a 70% by volume ethanol aqueous solution at 60° C. for 2 hours; then the natural material is treated in boiling distilled water for 1 hour, and dried in an oven at 70° C.;

[0078] Step S2, in-situ activation: 10 g of the natural material pretreated in step S1 is placed in a high-temperature cracking furnace chamber, and before the heat treatment begins, the air in the high-temperature cracking furnace chamber is replaced with high-purity argon gas, and then the chamber is closed and the air pressure in the chamber is adjusted to 0 MPa, and the furnace chamber is heated to 600° C. at a heating rate of 5° C. / min, and the sisal fiber is heat treated at this temperature for 2 hours; the high-temperature cracking furnace chamber is arranged to accommodate pyrolysis gas and prevent gas outside the chamber from entering;

[0079] Step S3, purification: the crude product prepared in step S2 is immersed in a 50% by volume ethanol aqueous solution at 60° C. for 2 h, the product is collected by filtration and dried in an oven at 50° C. to prepare a purified hierarchical porous carbon material.

[0080] Embodiment 2 of the present invention further provides an electrode sheet, which is prepared by the following method:

[0081] The graded porous carbon material purified in step S3 was mixed with a conductive agent and a binder in a mass percentage of 70:20:10, uniformly coated on an aluminum foil current collector sheet, and dried in an oven at 50° C. to prepare an electrode sheet.

[0082] The specific surface area of ​​the graded porous carbon material sample prepared by using sisal fiber in Example 2 of the present invention is 753 m 2 / g, and the mesopore content is 46.5%.

[0083] Example 3

[0084] Embodiment 3 of the present invention provides an in-situ activation preparation method of a hierarchical porous carbon material for an electrochemical energy storage device, the method comprising the following steps:

[0085] Step S1, pretreatment: soak the natural material (kapok fiber) in a 75% by volume ethanol aqueous solution at 60° C. for 2 h; then treat the natural material in boiling distilled water for 1 h, and dry it in an oven at 70° C.;

[0086] Step S2, in-situ activation: 10 g of the natural material pretreated in step S1 is placed in a high-temperature cracking furnace chamber, and before the heat treatment begins, the air in the high-temperature cracking furnace chamber is replaced with high-purity nitrogen, and then the chamber is sealed and the air pressure in the chamber is adjusted to 0.05 MPa, and the furnace chamber is heated to 900° C. at a heating rate of 10° C. / min, and the kapok fiber is heat treated at this temperature for 2 hours; the high-temperature cracking furnace chamber is arranged to accommodate pyrolysis gas and prevent gas outside the chamber from entering;

[0087] Step S3, purification: the crude product prepared in step S2 is immersed in a 70% by volume ethanol aqueous solution at 70° C. for 2 h, the product is collected by filtration and dried in an oven at 60° C. to prepare a purified hierarchical porous carbon material.

[0088] Embodiment 3 of the present invention further provides an electrode sheet, which is prepared by the following method:

[0089] The graded porous carbon material purified in step S3 was mixed with a conductive agent and a binder in a mass percentage of 80:15:5, uniformly coated on a copper foil current collector sheet, and dried in an oven at 60° C. to prepare an electrode sheet.

[0090] Figure 6 This is a surface scanning electron microscope image of the hierarchical porous carbon material prepared using kapok fibers in Example 3 of the present invention; Figure 6 As shown in Figure 2, the surface of the hierarchical porous carbon material prepared by kapok fiber formed uniformly distributed macropores / mesopores, and the specific surface area of ​​the sample was 1057 m 2 / g, and the mesopore content is 53.7%.

[0091] Example 4

[0092] Embodiment 4 of the present invention provides an in-situ activation preparation method of a hierarchical porous carbon material for an electrochemical energy storage device, the method comprising the following steps:

[0093] Step S1, pretreatment: soaking the natural material (jute fiber) in an ethanol aqueous solution with a volume fraction of 80% at 65° C. for 3 hours; then treating the natural material in boiling distilled water for 2 hours, and drying in an oven at 80° C.;

[0094] Step S2, in-situ activation: 30 g of the natural material pretreated in step S1 is placed in a high-temperature cracking furnace chamber. Before the heat treatment begins, the air in the high-temperature cracking furnace chamber is replaced with high-purity nitrogen, the chamber is sealed, and the air pressure in the chamber is adjusted to 0.1 MPa. The furnace chamber is heated to 1000° C. at a heating rate of 10° C. / min, and the jute fiber is heat-treated at this temperature for 3 hours. The high-temperature cracking furnace chamber is arranged to accommodate pyrolysis gas and prevent gas outside the chamber from entering.

[0095] Step S3, purification: the crude product prepared in step S2 is immersed in a 50% by volume ethanol aqueous solution at 60° C. for 2 h, the product is collected by filtration and dried in an oven at 50° C. to prepare a purified hierarchical porous carbon material.

[0096] Embodiment 4 of the present invention further provides an electrode sheet, which is prepared by the following method:

[0097] The graded porous carbon material purified in step S3 was mixed with a conductive agent and a binder in a mass percentage of 85:10:5, uniformly coated on a copper foil current collector sheet, and dried in an oven at 60° C. to prepare an electrode sheet.

[0098] Figure 7 This is a scanning electron micrograph of a longitudinal section of a hierarchical porous carbon material prepared using jute fibers in Example 4 of the present invention; as shown in the figure, uniformly distributed macropores / mesopores are formed on the surface of the internal pores of the hierarchical porous carbon material prepared using jute fibers, and the specific surface area of ​​the sample is 1216 m 2 / g, and the mesopore content is 56.2%.

[0099] Example 5

[0100] Embodiment 5 of the present invention provides an in-situ activation preparation method of a hierarchical porous carbon material for an electrochemical energy storage device, the method comprising the following steps:

[0101] Step S1, pretreatment: soak the natural material (bamboo fiber) in a 70% by volume ethanol aqueous solution at 60° C. for 2 hours; then treat the natural material in boiling distilled water for 2 hours, and dry it in an oven at 80° C.;

[0102] Step S2, in-situ activation: 40 g of the natural material pretreated in step S1 is placed in a high-temperature cracking furnace chamber, and before the heat treatment begins, the air in the high-temperature cracking furnace chamber is replaced with high-purity helium, and then the chamber is sealed and the air pressure in the chamber is adjusted to 0.15 MPa, and the furnace chamber is heated to 1000° C. at a heating rate of 10° C. / min, and the bamboo fiber is heat treated for 3 hours at this temperature; the high-temperature cracking furnace chamber is arranged to accommodate pyrolysis gas and prevent gas outside the chamber from entering;

[0103] Step S3, purification: the crude product prepared in step S2 is immersed in a 70% by volume ethanol aqueous solution at 70° C. for 2 h, the product is collected by filtration and dried in an oven at 60° C. to prepare a purified hierarchical porous carbon material.

[0104] Embodiment 5 of the present invention further provides an electrode sheet, which is prepared by the following method:

[0105] The graded porous carbon material purified in step S3 was mixed with a conductive agent and a binder in a mass percentage of 85:10:5, uniformly coated on a copper foil current collector sheet, and dried in an oven at 60° C. to prepare an electrode sheet.

[0106] Figure 8 This is a scanning electron microscope image of the interior of the hierarchical porous carbon material prepared by bamboo fiber in Example 5 of the present invention; as shown in the figure, the internal pore surface of the hierarchical porous carbon material prepared by bamboo fiber also forms uniformly distributed macropores / mesopores, and the specific surface area of ​​the sample is 1423m 2 / g, and the mesopore content is 60.3%.

[0107] In summary, the in-situ activation preparation method of a graded porous carbon electrode material for an electrochemical energy storage device disclosed in the present invention is used to solve the problems of low specific surface area, unreasonable pore structure, low macropore / mesopore content, complex production process, high product cost, and environmental unfriendliness of the porous carbon material for electrochemical energy storage devices prepared in the prior art. The present invention first uses an ethanol aqueous solution with a volume fraction of 70-80% and boiled distilled water to treat cellulose-based natural materials to remove wax and colloid on the surface of the natural material. Subsequently, the dried natural material is placed in a high-temperature cracking furnace and heat-treated under the condition of 0-0.15MPa inert gas to simultaneously achieve carbonization and in-situ activation of the natural material, thereby forming a macroporous-mesoporous-microporous graded pore structure carbon material. Next, the graded porous carbon material is treated with an ethanol aqueous solution with a volume fraction of 50-70% to remove tar attached to the surface of the material. Finally, the washed and dried porous carbon material is mixed with a conductive agent and a binder according to the mass percentage of (70-85): (10-20): (5-10) and evenly coated on a metal current collector such as aluminum foil or copper foil, and dried to obtain an electrode sheet suitable for supercapacitors, lithium-ion batteries, and sodium-ion batteries. The present invention provides a new preparation process for porous carbon materials for electrochemical energy storage devices and other fields that heavily rely on carbon materials with developed pore structures. The process is simple, short, and low in cost, and can effectively reduce environmental pollution and provide a new perspective for the utilization of pyrolysis gas.

[0108] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing hierarchical porous carbon materials by in-situ activation, characterized in that: The method comprises the following steps: Step S1, pretreatment: soaking the natural material in a 70-80% ethanol aqueous solution at 60-70° C. for 2-3 hours; The soaked natural materials are then treated in boiling distilled water for 1-2 hours and dried at 70-80°C; Step S2, in-situ activation: the natural material pretreated in step S1 is placed in a high-temperature cracking furnace chamber, and the natural material is heat-treated in the presence of 0-0.15 MPa inert gas; before the heat treatment begins, the air in the high-temperature cracking furnace chamber is replaced with inert gas, and no external gas is introduced into the high-temperature cracking furnace chamber during the heat treatment; Step S3, purification: the crude product prepared in step S2 is immersed in a 50-70% ethanol aqueous solution at 60-70°C for 2-3h, the product is collected by filtration and dried at 50-60°C to prepare a purified hierarchical porous carbon material.

2. The in-situ activation preparation method of a hierarchical porous carbon material according to claim 1, characterized in that: In step S1, the natural material types include: sisal fiber, jute fiber, kapok fiber or bamboo fiber.

3. The in-situ activation preparation method of a hierarchical porous carbon material according to claim 1 or 2, characterized in that: The inert gas includes: high-purity nitrogen, argon or helium.

4. The in-situ activation preparation method of a hierarchical porous carbon material according to claim 1, characterized in that: In step S2, the heat treatment conditions include: the heating rate of the high temperature cracking furnace chamber is 5-10°C / min, the heat treatment temperature is 600-1200°C, and the heat treatment time is 2-4h.

5. A hierarchical porous carbon material, characterized in that: The in-situ activation method is used to prepare the product.

6. An electrode sheet, characterized in that: The electrode sheet is prepared by the following method: The hierarchical porous carbon material according to claim 5 is mixed with a conductive agent and a binder, uniformly coated on a metal current collector sheet and dried at 50-60° C. to prepare an electrode sheet.

7. An electrode sheet according to claim 6, characterized in that: The mass percentage of the hierarchical porous carbon material to the conductive agent and the binder is (70-85): (10-20): (5-10).

8. An electrode sheet according to claim 6 or 7, characterized in that: The metal current collector is aluminum foil or copper foil.

9. An application of the electrode sheet according to any one of claims 6 to 8, characterized in that: The electrode sheet is applied to supercapacitors, lithium ion batteries or sodium ion batteries.

10. The use of an electrode sheet according to claim 9, characterized in that: In the application of supercapacitors, the electrode sheet is used as both a positive electrode sheet and a negative electrode sheet; In the application of lithium-ion batteries, the electrode sheet is a negative electrode sheet; In the application of sodium ion batteries, the electrode sheet is a negative electrode sheet.

11. The use of an electrode sheet according to claim 10, characterized in that: In the application of supercapacitors, the mass ratio of the positive electrode sheet to the negative electrode sheet is 1:1.